2014
DOI: 10.3103/s1541308x14030029
|View full text |Cite
|
Sign up to set email alerts
|

THz monitoring of the dehydration of biological tissues affected by hyperosmotic agents

Abstract: Different ways for monitoring the dehydration of tissues affected by hyperosmotic agents have been comparatively analyzed to increase the THz transparency of biological tissues. The data obtained with an original THz laser spectrometer, a Nicolet 6700 Fourier spectrometer, and a Callegari Soft Plus system for skin diagnostics are in good agreement. The corresponding responses of biological tissues (in the form of THz transmittance, reflectance, absorption coefficient, and hydration coefficient) to the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
(24 reference statements)
0
16
0
2
Order By: Relevance
“…It is important to notice that in vivo application of hyperosmotic agents on the skin causes strong dehydration of the superficial skin layers in a short time period (10‐20 minutes) . At these time intervals, the most part of the agents are concentrated in the epidermis.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to notice that in vivo application of hyperosmotic agents on the skin causes strong dehydration of the superficial skin layers in a short time period (10‐20 minutes) . At these time intervals, the most part of the agents are concentrated in the epidermis.…”
Section: Resultsmentioning
confidence: 99%
“…After obtaining the diffusion data for glucose and water on ex vivo tissues, we are planning to perform measurements in the future on an in vivo animal model to evaluate differences. However, based on our experimental data and direct measurements of tissue hydration for skin, 52 we can predict that tissue physiological reaction (which is delayed due to physiological reaction inertia) will correct the time response on a longer timescale. Nevertheless, we expect similar results to those obtained from ex vivo samples on a shorter time interval (<15 to 20 min).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 93%
“…and Kolesnikov et al. found that topical treatment of OCAs (30 % and 40 % glucose, glycerol, propylene glycol, Polyethylene glycol‐600) on human skin could induce different degrees of dehydration, and claimed that the skin transparent window existed from 10 to 22 min after OCA application. In our study, we applied a self‐made reservoir to keep the surface of skin immersed into the abundant reagent, thus the transparent skin window could be maintained for longer times to meet the need of imaging.…”
Section: Discussionmentioning
confidence: 99%